Single cell immune profiling by mass cytometry of newly diagnosed chronic phase chronic myeloid leukemia treated with nilotinib - Gullaksen, Stein-Erik; Skavland, Jørn; Gavasso, Sonia; Tosevski, Vinko; Warzocha, Krzysztof; Dumrese, Claudia; Ferrant, Augustin; Gedde-Dahl, Tobias; Hellmann, Andrzej; Janssen, Jeroen; Labar, Boris; Lang, Alois; et al. (Haematologica, 2017)
Monitoring of single cell signal transduction in leukemic cellular subsets has been proposed to provide deeper understanding of disease biology and prognosis, but has so far not been tested in a clinical trial of targeted therapy. We developed a complete mass cytometry analysis pipeline for characterization of intracellular signal transduction patterns in the major leukocyte subsets of chronic phase chronic myeloid leukemia. Changes in phosphorylated Bcr-Abl1 and the signaling pathways involved were readily identifiable in peripheral blood single cells already within three hours of the patient receiving oral nilotinib. The signal transduction profiles of healthy donors were clearly distinct from those of the patients at diagnosis. Furthermore, using principal component analysis, we could show that phosphorylated transcription factors STAT3 (Y705) and CREB (S133) within seven days reflected BCR-ABL1IS at three and six months. Analyses of peripheral blood cells longitudinally collected from patients in the ENEST1st clinical trial showed that single cell mass cytometry appears to be highly suitable for future investigations addressing tyrosine kinase inhibitor dosing and effect. (clinicaltrials.gov identifier: 01061177).
Keywords: Signal Transduction; Humans; fosforylace; bcr-abl fúzní proteiny; Pyrimidines; Single-Cell Analysis; chronická fáze myeloidní leukemie; signální transdukce; Leukocytes; tyrosinkinasy; protein vázající cAMP responzivní element; analýza jednotlivých buněk; Protein-Tyrosine Kinases; pyrimidiny; STAT3 Transcription Factor; Phosphorylation; Fusion Proteins, bcr-abl; Leukemia, Myeloid, Chronic-Phase; transkripční faktor STAT3; lidé; leukocyty; Cyclic AMP Response Element-Binding Protein